Corporate Decisions: Theory and Practice - Amir Aktanuly Amanzholov (Theoretical Hypotheses and Empirical Results, 2025)
Corporate decisions are a key element of strategic management aimed at improving business efficiency. This article examines the theoretical foundations of corporate decision-making, the methodologies for their implementation, and the application of Kaizen and Lean systems in BI Group’s practice. Special attention is given to the impact of digital technologies and modern management approaches on decision-making processes.